The role of Bag2 in neurotoxicity induced by the anesthetic sevoflurane. Issue 5 (12th December 2018) - Qi, Jinlian; Jia, Yingping; Wang, Wenhua; Lu, Haibing; Wang, Yuan; Li, Zhengchen
Abstract: Sevoflurane is the most commonly used general anesthetic in pediatric patients. But preclinical studies indicate that sevoflurane could have neurotoxicity in newborn and old animals, and this raises concern regarding its safety. In this study, we explored the potential mechanisms of sevoflurane‐induced neurotoxicity in human SH‐SY5Y neuronal cells. We showed that prolonged exposure to 2% sevoflurane caused a significant increase in the Bag family protein Bag2 in a time‐ and dose‐dependent manner. We investigated the possible role of Bag2 upon exposure to sevoflurane by silencing Bag2 in neuronal cells. Knockdown of Bag2 caused increased overall reactive oxygen species (ROS) and generation of lipid peroxidation products 4‐hydroxynonenal (4‐HNE). Upon sevoflurane exposure, Bag2‐silent cells have reduced glutathione (GSH) and glutathione peroxidase activity. Under the sevoflurane treatment, Bag2‐deficient cells have reduced mitochondrial membrane potential (MMP) and adenosine triphosphate (ATP) production, while knockdown cells have less viability and higher lactic dehydrogenase (LDH) release as well as a higher percentage of apoptotic cells. The knockdown cells also had higher levels of mitochondrial cytochrome C release, a higher ratio of Bax/Bcl‐2 and increased caspase cleavage by sevoflurane. Overall, our data support an important role of Bag2 in sevoflurane‐induced neurotoxicity.